Active site engineering by surface sulfurization for a highly efficient oxygen evolution reaction: a case study of Co3O4 electrocatalysts. Issue 45 (6th November 2018) - Pan, Ying; Ren, Hangjuan; Du, Haiwei; Cao, Fuyang; Jiang, Yifeng; Du, Haojin; Chu, Dewei
Abstract : Enhanced catalytic activity of Co3 O4 @CoS x through surface sulfurization. Abstract : In this work, a surface sulfurization strategy is utilized to construct Co3 O4 @CoS x heterogeneous catalysts with a highly efficient activity towards the oxygen evolution reaction (OER), and the enhanced catalytic activity is dependent on the degree of surface sulfurization. It is found that forming amorphous CoS x on the Co3 O4 surface through surface anion exchange can effectively generate more Co 2+ ions and oxygen vacancies in the lattice structure, not only inducing the production of more CoOOH but also facilitating water adsorption during the water oxidation process.